Reflexões sobre uma experiência em projetos terapêuticos singulares a partir do discurso de usuários - Ávila, Fátima Amorim (2014)
The Center for Psychosocial Care (CPC) is an attention device related at paradigm between care and assistance in patients with psychological distress. In this way, the Therapeutic Project Singular ( TPS ) should rescue the "personalized care" that is expressed as a main strategy of the organization and care in mental health services. This study was conducted at Izilda Maria da Silva (CPC I SP ) whose objectives were described bellow: Identify the impacts occurring to participants after insertion of Therapeutic Project Singular; analyze which aspects are perceived as boosters or those it could hinder the attendance; provide support for interventions according to the needs of the individual with mental distress.It was used four service users in this study. Data collection was performed by the Reflexive Interview and speeches that were analyzed using thematic analysis. Our results revealed that TPS contributed in the improvement of its users by reduced the number of hospitalizations, as well as established greater social integration; however it is still far from promoting the patients in their own care agents. The aspects of TPS enhancers were linked to application activities and others activities that reduced the verbal modality. In this scene, we emphasize the importance of training and supervision of the staff workers; the systematic reevaluation of the TPS; the effective implementation of a network of services concerning the reality of the city, as well as implementing intersectional or multicentre that include the Education, Culture and Social Promotion